Sheikh Muhammad Yasin al-Fadani’s Contribution to the 20th Century Nusantara-Haramain Ulama Intellectual Network in Manuscript Al-'Iqdu al-Farid min Jawahir al-Asanid - Imawan, Dzulkifli Hadi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
This study examines the intellectual network of Nusantara ulama (Muslim scholars) through the chain of transmission (sanad) found in Sheikh Muhammad Yasin al-Fadani’s al-Iqdu al-Farid min Jawahir al-Asanid. Sheikh Muhammad Yasin al-Fadani was a prominent Muslim scholar in Mecca and of Minangkabau descent. He was renowned for his extensive knowledge of the intellectual networks of Muslim scholars worldwide in the 20th century. Hence, this study investigates Sheikh Muhammad Yasin al-Fadani’s contributions to the intellectual network of Nusantara scholars with the scholars of Haramain, focusing on the manuscript al-Iqdu al-Farid min Jawahir al-Asanid. This study utilized a literature review to analyze Sheikh Muhammad Yasin al-Fadani’s contributions and his manuscript. The findings of this research explain that Sheikh Muhammad Yasin al-Fadani’s al-Iqdu al-Farid min Jawahir al-Asanid provides crucial information regarding the intellectual network of Nusantara ulama with those in Haramain and the Middle East in the 20th century. It successfully revealed their expertise in various Islamic studies disciplines and their contributions to scholarly development.